Numerical simulation study on mesoscopic mechanism of fracture evolution of slag-loess-based cemented backfill material - Liu, Tao; Chen, Liang; Wu, Peng; Zhang, Kai; Zhang, Lianying; Jiang, Tao; Fu, Lianjie (Frontiers in Materials, 2025)
Backfilling in underground mining is a widely adopted technique, often employing cement-based or geopolymer materials. However, the high cost and logistical challenges associated with these materials in remote mining locations necessitate alternative solutions. Loess materials offer a viable option for reducing production expenses and mitigating environmental impact. Despite this, the mechanical properties of loess-based cemented materials have been insufficiently investigated. This study introduces a novel slag-loess-based cemented backfill material. A three-dimensional model of the backfill material was constructed using Avizo software, and a numerical calculation model, incorporating the actual three-dimensional geometry of aggregate particles, was developed using PFC3D software. The influence of confining pressure σ3, curing temperature TC, and age TA on the crack evolution, force chain evolution, and particle failure characteristics during the loading process of the cemented backfill material was systematically examined. Results demonstrate that increasing confining pressure σ3 accelerates crack initiation and propagation, concurrently increasing the maximum value of the dominant force chain within the specimen at each stage. An increase in age TA has a limited effect on the proportion and quantity of final tensile-shear cracks, though it does intensify the specimen’s ultimate shear failure tendency. At lower curing temperatures (5°C), a significant impact on crack formation is observed, with this effect diminishing as curing temperature TC increases. The macroscopic failure modes of the specimens, across varying temperatures, predominantly exhibit shear failure.